Advances in Hepatic Tissue Bioengineering with Decellularized Liver Bioscaffold - Erik Aranha Rossi; Luiz Fernando Quintanilha; Carolina Kymie Vasques Nonaka; Bruno Solano de Freitas Souza (Stem Cells International)
The burden of liver diseases continues to grow worldwide, and liver transplantation is the only option for patients with end-stage liver disease. This procedure is limited by critical issues, including the low availability of donor organs; thus, novel therapeutic strategies are greatly needed. Recently, bioengineering approaches using decellularized liver scaffolds have been proposed as a novel strategy to overcome these challenges. The aim of this systematic literature review was to identify the major advances in the field of bioengineering using decellularized liver scaffolds and to identify obstacles and challenges for clinical application. The main findings of the articles and each contribution for technique optimization were highlighted, including the protocols of perfusion and decellularization, duration, demonstration of quality control—scaffold acellularity, matrix composition, and preservation of growth factors—and tissue functionality after recellularization. In previous years, many advances have been made as this technique has evolved from studies in animal models to human livers. As the field develops and this promising technique has become much more feasible, many challenges remain, including the selection of appropriate cell types for recellularization, route of cell administration, cell-seeding protocol, and scalability that must be standardized prior to clinical application.